THE EFFECT OF TECHNOLOGY-ORGANIZATION-ENVIRONMENT (TOE) ON E-COMMERCE ADOPTION AMONG SMES AT MAGELANG REGENCY - Suci Ayu Sudari (Klabat Journal of Management, 2023)
The purpose of this study is to investigate and analyze the influence of Technology-Organization-Environment (TOE) factors on the adoption of E-Commerce among Small and Medium-sized Enterprises (SMEs) in Magelang Regency. The research employs regression analysis as the primary method to evaluate the relationships between the independent variables—Technology, Organization, and Environment—and the dependent variable, E-Commerce Adoption. To gather primary data, a questionnaire was utilized as the data collection instrument. The population of interest consisted of 1080 SMEs within Magelang Regency, from which a representative sample of 100 SMEs was selected using the Slovin formula. Subsequently, the collected data was processed using SPSS version 23. The findings of the study demonstrated a positive and significant effect of the TOE factors on E-Commerce Adoption among SMEs in Magelang Regency. This research contributes to a deeper understanding of the dynamics and determinants of E-Commerce adoption in the specific context of SMEs within the mentioned region, highlighting the crucial role of Technology, Organization, and Environment in shaping adoption patterns. Keywords: Technology, Organization, Environment, E-Commerce, SMEs